2020
DOI: 10.1111/micc.12656
|View full text |Cite
|
Sign up to set email alerts
|

Coronary microvascular dysfunction in hypertrophic cardiomyopathy: Pathophysiology, assessment, and clinical impact

Abstract: Myocardial ischemia constitutes one of the most important pathophysiological features in hypertrophic cardiomyopathy. Chronic and recurrent myocardial ischemia leads to fibrosis, which may culminate in myocardial dysfunction. Since the direct visualization of coronary microcirculation in vivo is not possible, its function must be studied indirectly. Invasive and noninvasive techniques allow microcirculatory dysfunction to be evaluated, including echocardiography, magnetic resonance, positron emission tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 121 publications
1
36
0
3
Order By: Relevance
“…As expected, at a high level, our results show that cardiomyocyte hypertrophy, myocardial and cardiac remodeling, and myocardial fibrosis; AF and SCD; coronary microvascular dysfunction and myocardial ischemia; myocardial ischemia and HF share similar molecular mechanisms, which is in line with clinical literature findings on HCM progression [ 87 , 88 ], arrhythmic nature and association between AF and SCD [ 89 , 90 , 91 ], ischemic nature and association between coronary microvascular dysfunction and myocardial ischemia [ 25 , 92 , 93 ], and association between myocardial ischemia and HF in HCM [ 94 , 95 ]. The results suggest a more isolated (distinctive) nature of myofibrillar and cardiomyocyte disarray, impaired myocardial relaxation, and myocardial stiffness, which might be, to some extent, a consequence of the relatively low number of articles available and statements extracted, which then reduce the ability to identify the most important molecular elements.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As expected, at a high level, our results show that cardiomyocyte hypertrophy, myocardial and cardiac remodeling, and myocardial fibrosis; AF and SCD; coronary microvascular dysfunction and myocardial ischemia; myocardial ischemia and HF share similar molecular mechanisms, which is in line with clinical literature findings on HCM progression [ 87 , 88 ], arrhythmic nature and association between AF and SCD [ 89 , 90 , 91 ], ischemic nature and association between coronary microvascular dysfunction and myocardial ischemia [ 25 , 92 , 93 ], and association between myocardial ischemia and HF in HCM [ 94 , 95 ]. The results suggest a more isolated (distinctive) nature of myofibrillar and cardiomyocyte disarray, impaired myocardial relaxation, and myocardial stiffness, which might be, to some extent, a consequence of the relatively low number of articles available and statements extracted, which then reduce the ability to identify the most important molecular elements.…”
Section: Discussionsupporting
confidence: 89%
“…The clinical presentation of HCM varies widely [ 1 , 3 , 7 , 8 ]: some patients are asymptomatic [ 1 , 7 , 13 ], while others manifest symptomatic left ventricular outflow tract obstruction (LVOTO) [ 7 , 8 ], atrial fibrillation (AF) [ 3 , 8 ], sudden cardiac death (SCD) [ 3 , 7 , 13 , 14 ], or heart failure (HF) [ 1 , 3 , 10 , 11 ]. Pathophysiologic features of HCM include cardiomyocyte hypertrophy [ 15 , 16 ], cardiomyocyte disarray [ 16 , 17 ], myocardial remodeling [ 18 , 19 ], fibrosis [ 3 , 20 , 21 ], myocardial hypercontractility [ 22 , 23 ], impaired myocardial relaxation [ 20 , 24 ], myocardial stiffness [ 17 , 20 ], diastolic dysfunction [ 13 , 14 , 17 ], coronary microvascular dysfunction [ 25 , 26 ], and myocardial ischemia [ 25 , 27 ], but the underlying molecular mechanisms are poorly understood. Molecular determinants of the disease presentations are also still not known.…”
Section: Introductionmentioning
confidence: 99%
“…In hypertrophic cardiomyopathy (HCM), myocardial ischemia has been suggested to contribute to the pathophysiology of the disease, and appears to be related to decreased subendocardial perfusion in the hypertrophied segments, compression of intramural small vessels and myocardial bridging ( 59 ). Microvascular ischemia is thought to be involved in the development of adverse ventricular remodeling, and diastolic and systolic dysfunction, impacting clinical outcomes in adults and children ( 60 64 ). NMPI can contribute as a reliable non-invasive methods for the detection of myocardial ischemia, adding to risk stratification and treatment ( 59 , 62 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Further studies revealed that subendocardial ischemia might be one of the pathophysiological mechanisms underlying CMD-related HFpEF [54,55]. Reduced capillary density and vascular remodeling and fibrosis lead to a decrease in the coronary blood flow reserve, which in turn results in the development of hypertrophic cardiomyopathy and is closely associated with adverse prognosis [56][57][58][59]. Takotsubo cardiomyopathy, also referred to as stress-induced cardiomyopathy or broken heart syndrome, presents as acute, transient, and reversible systolic dysfunction of the left ventricle [60,61], and is strongly associated with CMD.…”
Section: Clinical Implications Of Cmdmentioning
confidence: 99%